2013
DOI: 10.1037/a0034533
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Predictors of Self-Reported Physical Aggression: Exploring Theoretically Relevant Dimensions Among Adolescents From Santiago, Chile

Abstract: Research findings remain unclear on whether different factors predict aggression for adolescent men and women. Given that aggression research is rarely conducted with Latin American populations, the current study used multiple imputation and linear regression to assess gender differences in levels and predictors of self-reported physical aggression among a community sample of young (ages 11 through 17) men (n=504) and women (n = 471) from Santiago, Chile. Results revealed that adolescent women reported engagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
10
0
2
Order By: Relevance
“…The present results are also supported by Smritikana Mitra Ghosh (2012) who did not find any significant difference in aggression between girls and boys in his study. , Barbara Krahe et al (2005), Vives and Colet (2010) and Fries et al (2013) were significantly more relationally aggressive or hostile than males. However, we did not find females as significantly higher than males on aggression, but results suggest both are equal on aggression.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The present results are also supported by Smritikana Mitra Ghosh (2012) who did not find any significant difference in aggression between girls and boys in his study. , Barbara Krahe et al (2005), Vives and Colet (2010) and Fries et al (2013) were significantly more relationally aggressive or hostile than males. However, we did not find females as significantly higher than males on aggression, but results suggest both are equal on aggression.…”
Section: Resultsmentioning
confidence: 88%
“…The data was collected by using Bullying victimization scale (BVS) and the results indicated that boys average score was higher than girls. Fries et al (2013) conducted a study Gender segregations in analyzing of Self-Reported Physical violence within Adolescents from Santiago, Chile within a community sample of youngsters (ages groups 11 -17). The sample consisted of men and women and the results discovered that teenager women reported engaged more in physical hostility than men.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Socioeconomic status risk factors include low socioeconomic status, exposure to community violence, drug use in the community, community disorganization, having five or more siblings, and living in a neighborhood where young people are in trouble. [17][18][19]22,24,27,[30][31][32][35][36][37][45][46][47][49][50][51][52]55,57, Clinical characteristics (Table 4) associated with correlates for violence in adolescents were organized into the following categories: substance use; depressive symptoms; attention deficit hyperactivity disorder (ADHD); impulse control; temperament and personality trait; and psychopathy. Cigarette, alcohol, and other illicit substances were found to be risk factors and can be classified under substance use.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…When 13-15-year-old boys were asked if they had participated in a physical fight at least once in the last year, over 50% of boys in Peru answered affirmatively (UNICEF, 2014). Girls in the region report relatively high rates of physical fights as well (Fries, Grogan-Kaylor, Bares, Han & Delva, 2013). When asked how many had been robbed in that same time frame, just over 50% of sixth graders across those 16 countries answered affirmatively, with the highest rate reported in Colombia (55%) and the lowest in Cuba (11%).…”
Section: Non-violent Horse-handling Workhops In Guatemalamentioning
confidence: 89%